Pengaruh Financial Literacy, Locus Of Control, dan Hedonism Lifestyle terhadap Financial Management Behavior - Alifah Sabrina Puteri Nur; Sari Andayani (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Technological advancements coupled with easier access to various digital financial services have impacted how students manage their money. This phenomenon deserves investigation, particularly among Kartu Indonesia Pintar Kuliah (KIP-K) recipients who receive educational funding assistance and must handle their finances intelligently. This study intends to examine the effects of financial literacy, locus of control, and hedonism lifestyle on financial management behavior among Accounting students at UPN “Veteran’’ Jawa Timur who are KIP-K recipients during the 2021–2024 period. The research methodology employed is quantitative, utilizing primary data collected through questionnaires. The study sample reached 131 respondents determined via purposive sampling technique. For data analysis, multiple linear regression method was applied using IBM SPSS Statistics 27 software. Based on the research findings, it was concluded that financial literacy does not produce a significant effect on financial management behavior. In contrast, locus of control and hedonism lifestyle demonstrate positive and significant effects on financial management behavior. These results indicate that students' self-control and lifestyle habits are more dominant in determining financial management behavior compared to the financial knowledge they possess. It is hoped that this research can serve as a reference for higher education institutions and students to improve the quality of financial management through strengthening self-control capabilities and developing more responsible lifestyle patterns.